Blockchain for Long-Term Digital Archiving in Academic Libraries: Preserving Authenticity and Accessibility - Ailakhu, Ugonna Vivian (Access: An International Journal of Nepal Library Association, 2025)
This paper explores the application of blockchain technology in digital archiving, emphasising its potential to preserve the authenticity and accessibility of digital records in academic libraries. Blockchain’s inherent immutability and decentralised structure in academic libraries offers a secure foundation for archiving, enabling enhanced protection against unauthorised alterations and facilitating trust in long-term digital preservation. It highlights critical advantages of integrating blockchain with archival practices, such as the reinforcement of data integrity through cryptographic protocols and distributed validation mechanisms. Additionally, case studies demonstrate blockchain's capability to support secure data sharing across borders and institutions, addressing common archival challenges. Despite its promise, the technology poses regulatory and legal obstacles, especially regarding data privacy and compliance with laws like the GDPR. This paper argues that while blockchain provides an innovative solution for digital archiving, a cautious approach is needed to balance its benefits with regulatory compliance. Future research should focus on refining blockchain-based archival frameworks to overcome these challenges and enhance usability for diverse stakeholders.